Organic and Functional Dysphonias: Comparison of Self-Assessment Protocols by Confirmatory Factor Analysis - Yasar, Ozlem Cangokce; Tahir, Emel; Kemal, Özgür; Dünder, Emre (Taylor & Francis Ltd, 2024)
Objective This study aims to see if the effects of the sub-domains of the Voice Handicap Index-10 (VHI-10) and Voice Related Quality of Life (VRQoL) differ in organic (OD) and functional dysphonia (FD). Method A total of 162 patients completed the validated Turkish versions of the Voice Handicap Index-10 (VHI-10) and Voice-Related Quality of Life (VRQoL). Physical (pVHI-10), emotional (eVHI-10) and functional (fVHI-10) sub-domains of VHI-10 and physical-functional (PF-VRQoL), socio-emotional (SE-VRQoL) dimensions of VRQoL were assessed. Confirmatory factor analysis (CFA) was used to compare the sub-domains of these questionnaires between diagnostic categories. Results The total and sub-domain scores of both VHI-10 and VRQoL were not statistically different between the two etiologic categories of dysphonia (MANOVA, p > .05). The total VHI-10 and total VRQoL scores were significantly and moderately correlated in both the OD and FD groups. During CFA, 4 models were constructed for the OD and FD groups for VHI-10 and VRQoL factors. There was no significant difference between OD and FD groups in terms of path coefficients of sub-domains (z test, p > .05). Conclusion In terms of VHI-10 and VRQoL, the sub-domains of each questionnaire are equally important in both organic and functional dysphonia. Functional disorders do not depend only on "emotional" factors, and neither do organic problems. Factor analysis should be included when performing a study on patient-reported outcome measures.
Yaşar, Özlem/0000-0003-4548-5964; Tahir, Emel/0000-0002-5219-0542; Kemal, Ozgur/0000-0002-6419-6204
Keywords: Dysphonia; Voice Disorders; Factor Analysis; Quality of Life; Voice Assessments; Measures